Who dragged Christianity into the AWARE Saga? Observations on the role of Christians, value pluralism and contestation in public discourse - EUGENE, Tan K. B. (Institutional Knowledge at Singapore Management University, 2011)
With 85 per cent of Singaporeans professing to belong to a religion, religion forms a core part of many Singaporeans’ identities and value systems. That religion and politics are not distinct and mutually exclusive spheres of influence and experience is also recognised by the state. The Association of Women for Action and Research (AWARE) dispute started quite innocuously, with initial indications being that of an internal spat that occurs once in a while in the nascent civil society space. As it is well-known by now, a group of relatively new and unknown members (the “new guard”) assumed control of AWARE at its annual general meeting in March 2009. The long-established stalwarts (the “old guard”) complacently failed to see the signs when applications for new memberships spiked in the lead up to the annual general meeting. But this was no ordinary leadership change or renewal. The installation of the new leadership in AWARE set in motion a series of events, culminating in the hot-tempered extraordinary general meeting (EGM), called by the old guard, in May 2009.